The Lonely Guy - Hiller, Arthur; Grodin, Charles; Judith Ivey; Steve Lawrence; Steve Martin (USA Aspen Film Society, 1984)
When shy Larry Hubbard finds his girlfriend in bed with another man he is forced to begin a new life as single. But since he can't bear being on his own he tries to court Iris who is not however interested in him. Larry begins writing a book on his experience as a single which unexpectedly becomes a best seller. He becomes rich and famous and even his relationship with Iris can begin on a new basis.
A writer for a greeting card company learns the true meaning of loneliness when he comes home to find his girlfriend in bed with another man.
Bruce Jay Friedman
Language : English Subtitles : English, French, Spanish
Keywords: Comedy